Rhetorical structures and linguistic features of English abstracts in Thai Rajabhat University journals - Thi Thuy Loan Nguyen (Penerbit Universiti Kebangsaan Malaysia, 2018)
Abstracts are an essential part of research articles (RAs) because they are the readers’ first encounter in their search for relevant literature. Writing an effective abstract in English which can “sell” the article to a wider circle of readers is therefore important to novice writers, especially multilingual ones. Based on the corpus of 584 English abstracts of Thai empirical RAs published by six Rajabhat (teacher-training) university journals which are indexed in the Thai-journal citation index center (TCI), this study aims to explore not only their rhetorical structures but also the grammatical and interactional metadiscourse features. The results show that there were three types of abstracts (Informative, Indicative and Combinatory) and the absence of certain moves in a large number of abstracts of each type. Moreover, this abstract corpus had a few instances of move embedding, a complete absence of move cycles and the existence of abstracts with several paragraphs. Regarding the linguistic features, there was a prominent presence of active voice, future tense and the sparing use of interactional meta-discourse devices across the moves. These findings tend to indicate a need for journal editors and novice writers, especially those from non-English backgrounds to be informed about the characteristics of good RA abstracts in English (i.e., rhetorically and linguistically) and an increased amount of form-based instruction in academic courses to address the linguistic deficiencies of new multilingual writers.